NEW CONCEPT OF PROFILE EDUCATION IN HIGH SCHOOL AND ITS INFLUENCE ON TRAINING OF FUTURE TEACHERS OF INFORMATICS - Mazur, Nataliia P. (Educological discourse, 2014)
In article review of the new Concept of profile education at profile school which was accepted on November 21, 2013 is offered; the short analysis of changes which it covers is carried out; division into profiles and their profilings is analysed available. Besides, the contents of programs for the subject “Information science” were considered at profile training in high school. It is specified, on the basis of what subject matters can be created necessary for competence for teaching of informatics and information technologies in high school.